Mechanical behaviour of jute fibre-reinforced polyester composite: Characterization of damage mechanisms using acoustic emission and microstructural observations. (October 2019) - Alia, Adem; Fantozzi, Gilbert; Godin, Nathalie; Osmani, Hocine; Reynaud, Pascal
The present work deals with the mechanical characterization of a woven jute fabrics reinforced polyester resin composite. Two stacking sequences were considered: [0]8 and [+45/−45]2S . In-situ acoustic emission technique, X-ray computed tomography (X-ray CT) and post-mortem microscopic observations were used to characterise the damage mechanisms and to follow their evolutions during uniaxial tension. The microstructural analysis and X-ray CT revealed the following damage modes for the two lay-ups: fibre-matrix debondings which constitute the dominant mechanism, matrix crackings and fibre breakages and pull-outs. The acoustic emission data were processed using an unsupervised pattern recognition technique which combines principal components analysis and k-means optimized by a genetic algorithm. Both temporal and frequential features of acoustic emission signals were considered. The Laplacian score and dendrogram were used to determine the relevant and uncorrelated descriptors for clustering. Three clusters of events were obtained and the waveforms of each one were examined. Furthermore, the frequency contents of signals of each cluster were accurately investigated using power density spectrum and smoothed pseudo Wigner-Ville time-frequency distribution and the discrepancies between clusters are highlighted. Cluster 1 (Cl 1) characterized by signals of low frequency and intermediate amplitude, cluster 2 (Cl 2) characterized by signals of higher frequency and an amplitude similar to that of Cl 1 and cluster 3 (Cl 3) characterized by signals of higher amplitude. A correlation between the clusters and the damage mechanisms was established by means of interrupted tensile tests: Cl 1 is assigned to the matrix cracking, Cl 2 to the fibre-matrix debonding and Cl 3 to the fibre breakage and pull-out. The kinetic of evolution of each damage mode was monitored for the two stacking sequences.